The success of the War on Drugs - Coelho, Thábata Ribeiro (Revista de Ciências do Estado, 2022)
There are a lot of analysis, inside and outside the academic environment, that claim, at some point, the failure of the War on Drugs. Most of the time, the use of the verb “fail” is for demonstrate disagreement with the current public policies when it comes to illicit drugs. However, it is necessary to ask: has the War on Drugs really failed? The objective of this article is to explore the perspective that points to the success of this criminal policy model from the beginning to the present day and, therefore, to expose that the results obtained in this war are not occasional or unwanted.